PENGARUH VARIASI PENGASAPAN SERAT SABUT KELAPA SEBAGAI KOMPOSIT TERHADAP KEKUATAN IMPACT - LA ODE ASMAN MURIMAN; AFDAL SYARIF; HASFANDI (POLITALA PRESS, 2022)
This study aims to determine the mechanical strength properties of coco fiber composites with changes in fumigation time versus impact strength. In this study, we used an experimental approach in which the 100 cm height non-fumigation coir composite was varied in fiber fumigation time for 3, 4, and 5 hours, and the strength of the fumigated coir composite was compared with that of the fumigated coir composite. fiber. compared to - Unfumigated composite materials. Based on the data analysis, the impact strength of the composite tends to decrease, with the fumigasion fiber having an impact value of 0.0404 J/mm2 at 3 hours and the fumigation fiber having an impact value of 0.0274 J/mm2 at 4 hours. has the fumigasion fiber for 5 hours per hour has an effect rate of 0.0241 J/mm2 and without smoking the effect rate is 0.0269 J/mm2.